Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.16451
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing analyses reveal novel differentially expressed genes and pathways in pancreatic cancer

Abstract: Gene expression microarrays have identified many tumor markers and therapeutic targets for pancreatic ductal adenocarcinoma (PDAC). However, microarray profilings have limited sensitivity and are prone to cross-hybridization between homologous DNA fragments. Here, we perform a transcriptome analysis of paired tumor and adjacent benign pancreatic tissues from 10 patients who underwent resection for PDAC. We identify a total of 2736 differentially expressed genes (DEGs) with false discovery rate less than 0.05, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
5
46
0
2
Order By: Relevance
“…Using TCGA RNA‐seq Level 3 data from four PDAC patients, we found that PAIP2B expression was downregulated in tumors (mean = 90.58) compared to paired normal tissues from the same patient (mean = 150.22) ( p = 0.23, paired t ‐test). This observation agreed with data from our previous RNA‐seq study on paired tumor‐normal tissues of ten PDAC patients, which showed a 7.8‐fold lower expression of PAIP2B in tumors than in normal adjacent tissues ( p = 0.00032) . Notably, the expression of PAIP2B was significantly reduced in tumors compared to that in normal adjacent tissues of other gastrointestinal cancers according to TCGA RNA‐seq data ( p 8×105) (Table ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Using TCGA RNA‐seq Level 3 data from four PDAC patients, we found that PAIP2B expression was downregulated in tumors (mean = 90.58) compared to paired normal tissues from the same patient (mean = 150.22) ( p = 0.23, paired t ‐test). This observation agreed with data from our previous RNA‐seq study on paired tumor‐normal tissues of ten PDAC patients, which showed a 7.8‐fold lower expression of PAIP2B in tumors than in normal adjacent tissues ( p = 0.00032) . Notably, the expression of PAIP2B was significantly reduced in tumors compared to that in normal adjacent tissues of other gastrointestinal cancers according to TCGA RNA‐seq data ( p 8×105) (Table ).…”
Section: Resultssupporting
confidence: 90%
“…The association of selected SNPs and gene expression levels was evaluated using Genotype‐Tissue Expression (GTEx) and NCBI eQTL database and the RNASeq Level 3 data from TCGA. A previously conducted RNA‐Seq study in paired normal and tumor tissues from ten patients with resected PDAC tumors was also considered.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, mRNA levels of a number of digestive enzymes appeared to be significantly reduced, such as casein alpha s1 (CSN1S1), perilipin 4 (PLIN4), perilipin 1 (PLIN1), and peptidase M20 domain containing 1 (PM20D1). This finding is consistent with previous observations, which reflect an impairment of exocrine pancreatic functions by the tumor . The majority of DEGs remained a consistent trend of gene expression changes in individual patients.…”
Section: Resultssupporting
confidence: 93%
“…Almost all of these studies used either cell lines or animal models of PC, or microarray‐based methods that have apparent limitations when compared with RNA‐seq techniques. Very recently, a small number of RNA‐seq‐based transcriptome analyses have been conducted to investigate the gene expression profile changes in pancreatic tissues between different groups of patients (eg, tumor vs non‐tumor, short‐survivor vs long‐survivor) . However, those preliminary studies did not fully demonstrate the complex mRNA‐miRNA interaction network and failed to identify genes and molecular mechanisms that may drive the pathogenesis of PC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an RNA sequencing assessment has complemented the list of the previous differently expressed genes in PC tumor samples in comparison to benign pancreatic tissue [34] . These data have been used for PC taxonomy purposes and clinical trial design.…”
Section: Tumor Rna Markersmentioning
confidence: 99%